Effects of Removal Conditions on Mercury Amount Remaining in the Oral Cavity and inside Drainage System after Removing Dental Amalgams - Ishida Yoshiki; Aoki Harumi; Miyasaka Taira; Aoyagi Yusuke; Miura Daisuke; Shinya Akikazu (MDPI, 2022)
Mercury is produced and drained into the environment by removing dental amalgams, which may cause mercury pollution. This study aimed to clarify the mercury amount remaining in the oral cavity and inside the drain system after removal. The effects of the removal conditions and differences in drainage systems were also investigated. Dental amalgams filled in the tooth and placed in a phantom head were removed using an air turbine under several conditions (two removal methods, absence of cooling water, and intraoral suction). Then, the oral cavity was rinsed with 100 mL of water (oral rinse water), and 500 mL of water was suctioned to wash the inside of the drainage system (system rinse water). Both water samples were collected in two ways (amalgam separator and gas-liquid separator), and their mercury amounts were measured. It was found that the amount of mercury left in the oral cavity and drainage system after dental amalgams removal could be reduced when the amalgams were removed by being cut into fragments as well as using cooling water and intraoral suction. In addition, using amalgam separators can significantly reduce the amount of mercury in the discharge water and prevent the draining of mercury into the environment.